(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study aims to analyze the changes in rhyme and rhythm as well as the thematic content of the qaṣīdah Faidhotul Man Min Rohmati Wahhabil Manan composed by Umar bin Muhammad bin Salim bin Hafidz, using the approach of ʿarūḍ (Arabic prosody) and qawāfī (rhyme theory). The qaṣīdah, as a form of classical Arabic poetry, features a distinctive metrical and rhyming structure that serves not only as an aesthetic element but also as a medium for conveying spiritual and religious messages. The research method employed is descriptive qualitative, using textual analysis techniques from Arabic literary studies. The analysis reveals that this qaṣīdah demonstrates variations in rhythm (wazn) and rhyme (qāfiyah) patterns while maintaining semantic coherence and the musical integrity of the poem. In terms of theme, the qaṣīdah contains praise for the Prophet Muhammad (peace be upon him), affirmation of divine mercy, and expressions of spiritual longing and submission to Allah.